Endometriosis Mimicking a Cecum Mass with Complete Bowel Obstruction: An Infrequent Cause of Acute Abdomen. (31st January 2019) - Molina, Gabriel A.; Ramos, Darwin R.; Yu, Alberto; Paute, Patricio A.; Llerena, Paul S.; Alexandra Valencia, S.; Fonseca, Jose V.; Morillo, Jhonatan F.; López, Sandra C.; Gutierrez, Bernardo M.
Abstract : Endometriosis is a common entity among fertile women which unfortunately manifests through variable symptomatology. Intestinal involvement in endometriosis is quite common and can simulate several diseases such as Crohn's disease, appendicitis, tubo-ovarian abscess, or malignant tumors. Intestinal obstruction due to endometriosis is rare, and preoperative diagnosis is difficult because the signs and symptoms are nonspecific and can be easily confused. In the case of patients without a history of endometriosis, diagnosis is further complicated. We present a case of a 41-year-old female patient. She presented to the emergency room with complete bowel obstruction and a mass in the cecum. Surgery was decided, and the patient underwent full recovery. Endometriosis was the final diagnosis for the observed condition.